2022
DOI: 10.1057/s41267-022-00583-x
|View full text |Cite
|
Sign up to set email alerts
|

Learning from inbound foreign acquisitions for outbound expansion by emerging market MNEs

Abstract: Although cross-border acquisitions (CBAs) are prevalent, many such acquisitions fail to complete. This challenge is even more profound for emerging market MNEs (EMNEs). Drawing upon the vicarious learning theory, we argue that EMNEs can learn from inbound foreign acquirers through the latter's demonstration, professional services firms, and employees. This learning mechanism enables EMNEs to better deal with the complexity and uncertainty in various stages of acquiring foreign firms, thus increasing the comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 128 publications
0
6
0
Order By: Relevance
“…This is also evident from the World Investment Report (WIR), which shows that CBAs initiated by EMNEs decreased from US$48.208 billion in 2018to $22.132 billion in 2019(UNCTAD, 2020. Prior studies often interpret expansion barriers based on the various types of home-host country distance (e.g., geographical, cultural, and institutional distance) (Bu et al, 2023;Wang et al, 2014). The most recent studies look at the ideological tension between countries, suggesting that national sentiments, especially the sense of nationalism, affect the completion and progress of CBAs (Lubinski & Wadhwani, 2020;.…”
Section: Our Research Question Ismentioning
confidence: 99%
See 2 more Smart Citations
“…This is also evident from the World Investment Report (WIR), which shows that CBAs initiated by EMNEs decreased from US$48.208 billion in 2018to $22.132 billion in 2019(UNCTAD, 2020. Prior studies often interpret expansion barriers based on the various types of home-host country distance (e.g., geographical, cultural, and institutional distance) (Bu et al, 2023;Wang et al, 2014). The most recent studies look at the ideological tension between countries, suggesting that national sentiments, especially the sense of nationalism, affect the completion and progress of CBAs (Lubinski & Wadhwani, 2020;.…”
Section: Our Research Question Ismentioning
confidence: 99%
“…The advent of deglobalization amplifies the complexity of firms' international expansion, especially for EMNEs that are more vulnerable to environmental varieties due to their limited prior experience and lack of understanding of the rules of the game in different countries (Luo & Witt, 2021). Although previous IB research examines the various forms of cross-country differences in hindering or facilitating EMNEs' internationalization (Bu et al, 2023;Wang et al, 2014), less is known about whether the intensified environmental variations due to the rise of nationalism affect their expansion. Nationalism has increasingly become a global strain in the last two decades 1 , characterized by 'an intolerance of criticism and an unquestioning positive evaluation of, and staunch allegiance to, one's own nation' (Hanson & O'Dwyer, 2019: 780).…”
Section: Moderating Effect Of Comparative Nationalismmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that if the controller in this paper is used in a higher order system it may lead to differential explosion. Te articles [33][34][35] provide solutions to this problem and interested authors can refer to them.…”
Section: Controller Designmentioning
confidence: 99%
“…From equation (34), it can be concluded that z 1 , z 2 , 􏽥 θ, and 􏽥 ρ are bounded. From reference [11], the boundedness of x 1 , x 2 , x 3 , and x 4 can be guaranteed.…”
Section: Controller Designmentioning
confidence: 99%